Sculpting a mobile musical soundtrack - Hazzard, Adrian; Benford, Steve; Burnett, Gary (2015)
We present an in-the-wild project to design and study a mobile musical soundtrack that enhances the experience of visiting a sculpture park. As with soundtracks for films and games, the goal was to enhance the emotional and narrative aspects of the experience while remaining in the background. We describe a compositional approach in which we first established a broad musical landscape before treating specific exhibits with detailed musical trajectories. Our study reveals how our soundtrack dramatically shaped visitors’ experiences while they remained largely unaware of its operation. We distil seven experiential factors to be addressed by mobile soundtracks alongside ten compositional guidelines.